Affective disorder: architectural design for complex national identities. Issue 4 (7th August 2020) - Pandya, Samir
ABSTRACT: Underpinned by concepts drawn from postcolonial theory, this article speculates on the relationship between built form and the experience of difference. It critically examines cultural theorist Homi K. Bhabha's conceptualisation of nation – focusing on ideas of the 'performative' and 'pedagogical' – as applied to frame specific works of architecture in the writing of Felipe Hernández. This analysis is then used as the foundation for two building reviews. Firstly, the National Museum of Australia, which reveals an emphasis on formal incoherence to reflect the plurality of national identity. This in-turn leads to a consideration of 'affect' as an alternative design hermeneutic in the pursuit of non-reductive methods to reflect the lived plurality of 'nation-space'. This consideration is extended to a second building study: the Institut du Monde Arabe, which is used to advance ideas on the relationship between form (representation) and affect (non-representation) and the relative merits these may bring to a re-thinking of design approaches in contexts of complex national identities.